2021
DOI: 10.1021/acsami.1c04046
|View full text |Cite
|
Sign up to set email alerts
|

Superhydrophobic and Recyclable Cellulose-Fiber-Based Composites for High-Efficiency Passive Radiative Cooling

Abstract: Passive daytime radiative cooling (PDRC) involves cooling down an object by simultaneously reflecting sunlight and thermally radiating heat to the cold outer space through the Earth's atmospheric window. However, for practical applications, current PDRC materials are facing unprecedented challenges such as complicated and expensive fabrication approaches and performance degradation arising from surface contamination. Herein, we develop scalable cellulose-fiber-based composites with excellent self-cleaning and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(86 citation statements)
references
References 28 publications
(43 reference statements)
1
66
0
Order By: Relevance
“…The cooling wood achieved continuous subambient conditions during the day and night (Figure 4b). Similarly, other cellulose‐based materials [ 35,41–48 ] as efficient IR emitters have been explored for PDRC. Tian et al.…”
Section: Development Of Advanced Pdrc Devicesmentioning
confidence: 99%
“…The cooling wood achieved continuous subambient conditions during the day and night (Figure 4b). Similarly, other cellulose‐based materials [ 35,41–48 ] as efficient IR emitters have been explored for PDRC. Tian et al.…”
Section: Development Of Advanced Pdrc Devicesmentioning
confidence: 99%
“…Interestingly, our PDMS sponge shows a thermal conductivity of 0.06 W (m K) −1 , which is the lowest value among recently reported radiative cooling materials and is suitable for building envelope. [ 11 , 29 , 48 , 49 ]…”
Section: Resultsmentioning
confidence: 99%
“…In fact, paper consisting of cellulose fibers (20–50 μm in diameter), as a material with high solar reflectivity ( R solar ) of about 0.89 and an excellent infrared thermal emissivity ( ε IR ) of 0.92, is a good candidate for passive daytime radiative cooling (PDRC). 155 Tian et al 147 reported the preparation of superhydrophobic paper-based composites with self-cooling and self-cleaning properties by coating poly(tetrafluoroethylene) (PTFE) particles with extremely high reflectivity and extremely low surface energy via physical adsorption and mechanical interaction. The superhydrophobic coating endowed the paper with self-cleaning properties and could avoid the reduction of radiative cooling performances caused by contaminations such as floating dust, dirt, and soot on the surface of the paper (Fig.…”
Section: Cellulose-based Papermentioning
confidence: 99%
“…The resultant self-cooling paper exhibited a subambient cooling performance of 5 °C under a solar irradiance of 834 W m −2 and a radiative cooling power of 104 W m −2 under a solar intensity of 671 W m −2 . 147 Moreover, the emergence of this radiative cooling paper not only can broaden the multifunctional applications of paper but also can pave the way for the development of energy-efficient and eco-friendly cooling systems.…”
Section: Cellulose-based Papermentioning
confidence: 99%